Jarosite versus Soluble Iron-Sulfate Formation and Their Role in Acid Mine Drainage Formation at the Pan de Azúcar Mine Tailings (Zn-Pb-Ag), NW Argentina - Murray, Jesica María (2014)
Secondary jarosite and water-soluble iron-sulfate minerals control the composition of acid mine waters formed by the oxidation of sulfide in tailings impoundments at the (Zn-Pb-Ag) Pan de Azúcar mine located in the Pozuelos Lagoon Basin (semi-arid climate) in Northwest (NW) Argentina. In the primary zone of the tailings (9.5 wt % pyrite-marcasite) precipitation of anglesite (PbSO4), wupatkite ((Co,Mg,Ni)Al2(SO4)4) and gypsum retain Pb, Co and Ca, while mainly Fe2+, Zn2+, Al3+, Mg2+, As3+/5+ and Cd2+ migrate downwards, forming a sulfate and metal-rich plume. In the oxidation zone, jarosite (MFe3(TO4)2(OH)6) is the main secondary Fe3+ phase; its most suitable composition is M = K+, Na+, and Pb2+and TO4 = SO42−; AsO42−. During the dry season, iron-sulfate salts precipitate by capillary transport on the tailings and at the foot of DC2 (tailings impoundment DC2) tailings dam where an acid, Fe2+ rich plume outcrops. The most abundant compounds in the acid mine drainage (AMD) are SO42−, Fe2+, Fe3+, Zn2+, Al3+, Mg2+, Cu2+, As3+/5+, Cd2+. These show peak concentrations at the beginning of the wet season, when the soluble salts and jarosite dissolve. The formation of soluble sulfate salts during the dry season and dilution during the wet season conform an annual cycle of rapid metals and acidity transference from the tailings to the downstream environment.